Tangential contact modeling to seal considering elastic-plastic for lubrication transition mechanism - Yin, Tuyuan; Sun, Dongning; Miao, Kefei; Liu, Huixiang; Tong, Xiaomeng; Xie, Zhongliang (Tribology international, 2025)
Researches on the reciprocating seals lubrication under elastic-hydrodynamic lubrication (EHL) are mature, and leakage of failure criterion has been described with Couette flow for more than 30 years, which could not reflect to leakage mechanism in multiscale. Thus, it is necessary to explore seal leakage failure to focus on micro convex bodies of asperities model under contact pressure and cycle tangential friction stress in mixed lubrication. This is because convex bodies behaviors determine sealing effect and lubrication behaviors in microscale with subjecting to the dominant pressure. Interaction between convex bodies fatigue hysteresis curve and elastic-plastic strain are also calculated to explore sealing effect with leakage rate mechanism. We then design water seal at high pressure of 100 MPa with the speed of 0.1–1 m/s and medium temperature from 5 ℃ to 40 ℃. IWAN model of the convex bodies are calculated. Probability density function and Jenkin’s elements critical slip displacement are obtained. Convex bodies of radial and tangential deformation are also calculated through loading of contact pressure and friction stress with cycle strength coefficient to obtain seal fatigue lifespan. Ratio to seal stick and slip friction is calculated for evaluating the loading boundary. Seal leakage failure mechanism with fatigue characteristics is illustrated with macro lubrication parameters and micro convex bodies mechanics performance. •Leakage failure mechanism is related to the contact behaviors of micro convex bodies with fatigue lifespan.•Convex bodies radial and tangential is calculated, and following Jenkin’s elements can obtain roughness probability density.•IWAN model of elastic and elastic-plastic deformation is solved based on FEM under contact pressure and tangential friction.•We combine mixed lubrication numerical method and convex bodies model to reveal seal leakage rate mechanism from the elastohydrodynamic lubrication.